Model Pembelajaran Interaktif Pada Mata Pelajaran Pendidikan Agama Islam (PAI) Dalam Meningkatkan Prestasi Belajar Siswa - Hafid Muslih; Ema Roslaeni (Program Studi Pendidikan Agama Islam, Universitas Muhammadiyah Bandung, 2024)
Interactive learning is one of the learning approaches that teachers can use when teaching. Teachers play an important role in creating an interactive educational atmosphere, where students can communicate with each other, with the teacher, and with their learning resources. Interactive learning is designed in such a way that the focus of learning is centered on students so that they can learn better and better understand what they are learning. This field research uses a descriptive qualitative approach and uses triangulation techniques to test the validity of the data. The result of the author's research is the answer to the formulation of the first problem: The implementation of interactive PAI learning requires Introduction, Implementation, and Closing activities. Second, a better understanding of translation, interpretation, and extrapolation is obtained through the interactive PAI learning model. Third, researchers found that the factors that support and hinder the use of interactive PAI learning to improve students' understanding at SDN Kertajaya Surabaya are as follows: a. Supporting factors include school leaders, teachers, students, and community leaders; b. Hindering factors include self, environment, and differences in students' backgrounds.